(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the symbolic significance of the dog mentioned in Surah Al-Kahf (18), focusing on its role in the story of the People of the Cave. The dog’s presence, particularly its posture as a vigilant guardian, highlights themes of loyalty, companionship, and divine protection. Through an analysis of the dog’s physical presence, its symbolic interpretations within Islamic tradition, and its theological implications, the article demonstrates how this animal serves as a powerful reminder of God’s mercy and the importance of unwavering faith. It also discusses the lessons contemporary Muslims can derive from this narrative, emphasizing humility, loyalty to righteous companions, and the recognition of inherent value in all creatures. Ultimately, the dog in Surah Al-Kahf is not merely a detail, but a crucial element that enriches the story and reinforces its spiritual messages.